(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
This proposal aims to show the results of a preliminary study about the edition Opere di Torquato Tasso colle controversie sopra la Gerusalemme liberata divise in sei tomi (Florence, 1724) published by Giovanni Gaetano Bottari. The study focuses especially on the editor’s correspondence in order to gather informations about the his choises and the way Bottari collected Tasso’s works for the opera omnia.